Callaccitra Undagi Mahottama: A Documentary Film on “Undagi” Bali as a Cultural Heritage Digital Repository Content - Noorwatha, I Kadek Dwi; Prabhawita, Gede Basuyoga; Puriartha, I Kadek (Jurnal Bali Membangun Bali, 2023)
Abstract Purpose: A film entitled Calaccitra Undagi Mahottama (CUM) is used as a model for documenting cultural actors, as a starting point and inspiration for the development of a culture-based creative industry, as suggestions on synergies between villages, local governments, educational institutions, and centers in cultural conservation with digital cultural heritage repositories. Research methods: This descriptive research empirically examines objects with a qualitative-analytic approach. The research inductively dissects the film CUM as a case object, from concept to process, and then synthesizes a documentary film formulation as a solution to preserving Balinese culture through RDWB. Findings: Synergy Scheme Map of the Village Video Movement with the Cultural Heritage Digital Repository, with CUM movie as a pilot project. The position of CUM's documentary films is to prioritize cultural preservation through biographical historical information with a historical approach. Bali needs more data collection on cultural resource assets in villages that still need to be appointed. Implication: The position of the Provincial Government of Bali is to be the leading actor, apart from being the initiator and also the leading actor in the process, supported by educational institutions and related social institutions as cultural curators.